2001
DOI: 10.1051/vetres:2001147
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical detection of the lectin-binding carbohydrates in the zona pellucida during oocyte growth in the wild boar (Sus scrofa scrofa)

Abstract: -The changes that occur in the carbohydrate composition of zona pellucida glycoproteins during oocyte maturation in the wild-boar were studied using periodic-acid Schiff (PAS), High Iron Diamine (HID) and Low Iron Diamine (LID). Lectin staining was performed with a panel of 11 HRPlectin conjugates combined with neuraminidase digestion and chemical treatments. There were few internal glucidic residues, such as N-acetylglucosamine, in the wild boar zona pellucida but there were many subterminal β-N-acetylgalacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In the present study, we investigated the histochemical characteristics of the ZP of the ovarian follicles of Lagostomus maximus , and its variations in NPr and Pr females, using histochemical and lectin histochemical techniques. The results, obtained at the ZP using the histochemical PAS and AB at different pH techniques, do not differ from those described by studies carried out in other mammals species, such as Mus musculus (Kaufman, Fowler, Barratt, & McDougall, ; Shimizu & Yamada, ), Mesocricetus aureatus (Delgado & Zoller, ), Sus scrofa scrofa (Parillo, Diverio, Todini, & Fagioli, ), Melanorivulus punctatus (Cassel, Mehanna, Mateus, & Ferreira, ) and even in other hystricomorphic rodents such as Myocastor coypo (Felipe, Cavodevila, & Callejas, ). The α‐amylase‐PAS, K(OH)/PA*/Bh/PAS and PA/Bh/KOH/PAS techniques were used to study the presence of sugars, usually in organs that produce different types of mucins, since they allow differentiating certain features of a specific portion of carbohydrates (Lev & Spicer, ; McManus, ; Pearse, ; Reid, Culling, & Dunn, ; Volz, Reid, Park, Owen, & Dunn, ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, we investigated the histochemical characteristics of the ZP of the ovarian follicles of Lagostomus maximus , and its variations in NPr and Pr females, using histochemical and lectin histochemical techniques. The results, obtained at the ZP using the histochemical PAS and AB at different pH techniques, do not differ from those described by studies carried out in other mammals species, such as Mus musculus (Kaufman, Fowler, Barratt, & McDougall, ; Shimizu & Yamada, ), Mesocricetus aureatus (Delgado & Zoller, ), Sus scrofa scrofa (Parillo, Diverio, Todini, & Fagioli, ), Melanorivulus punctatus (Cassel, Mehanna, Mateus, & Ferreira, ) and even in other hystricomorphic rodents such as Myocastor coypo (Felipe, Cavodevila, & Callejas, ). The α‐amylase‐PAS, K(OH)/PA*/Bh/PAS and PA/Bh/KOH/PAS techniques were used to study the presence of sugars, usually in organs that produce different types of mucins, since they allow differentiating certain features of a specific portion of carbohydrates (Lev & Spicer, ; McManus, ; Pearse, ; Reid, Culling, & Dunn, ; Volz, Reid, Park, Owen, & Dunn, ).…”
Section: Discussionsupporting
confidence: 59%
“…The positive staining observed with the WGA lectin indicates that ZP of the ovarian follicles of both groups could contain N‐acetylglucosamine (GlcNAc). This glycosidic residue is also present in the ovarian follicles ZP of other mammals such as the rat (Avilés, Martinez‐Menarguez, Castells, Madrid, & Ballesta, ; Barbeito et al, ), the mouse (Shimizu & Yamada, ) and the wild boar (Parillo et al, ). This residue is related to the process of initial recognition of the sperm–ovule, where the superficial enzyme of the male gamete 1,4‐galactosyltransferase (GalTase)‐ binds to GlcNAc present in one of the three constitutive glycoproteins of the mouse ZP, a species in which fertilization of mammals has been best characterized (Miller, Decker, & Shur, ).…”
Section: Discussionmentioning
confidence: 97%
“…These neutral sugars may be contributed to protective function, acting in neutralizing gastric acidity and may transport macromolecules across cell membrane (Domenoghini et al, 1998and Parillo et al, 2001. This may augment our results in that most of the lectins used in our study produced similar staining intensities in oxyntic cells (labeling of the intracellular membrane system and of the plasma membrane) and chief cells (labeling of the apical plasma membrane).…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, assuming that the sialic acid acetylation enhances the resistance to bacterial breakdown of glycans (Mastrodonato et al, ), it can be hypothesized that the decrease in staining intensity of goblet cells with the PA/Bh/KOH/PAS technique in the ileum of the viscacha could reduce the resistance of these mucins against bacterial sialidase; nevertheless, the protective role in this intestinal region could probably be played by highly sulfated mucins. Previous studies have demonstrated that the presence of sulfate groups in an oligosaccharide chain can interfere with lectin–sugar interactions (Menarguez‐Martinez et al, ; Parillo et al, ). In this study, some differences were detected between the histochemical and lectin‐histochemical results.…”
Section: Discussionmentioning
confidence: 99%